Technology Integration in Education Management: A Systematic Review of Scopus-Indexed Studies (2020–2024) - Cheriani Cheriani; Harmita Sari; Romi Adiansyah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid integration of digital technologies has significantly transformed educational management practices. However, the specific roles and functions of technology across different educational levels remain insufficiently synthesized. This study aims to review technology integration in educational management and examine its functional roles in supporting learning and institutional objectives. A systematic literature review was conducted following the PRISMA framework. Data were retrieved from the Scopus database, covering publications from 2020 to 2024. Bibliometric and thematic analyses were performed using VOSviewer to identify trends, patterns, and focal areas of technology use in educational management. The findings indicate that technology in educational management is predominantly applied to support learning processes, particularly through assessment systems and technology-enhanced instructional strategies that improve student comprehension. However, the review also reveals notable differences between schools and universities in their technological objectives, reflecting diverse institutional priorities and levels of implementation. The study highlights that technology fulfills multiple and context-dependent functions within educational institutions. Consequently, curriculum development and educational policy design should not be generalized across educational levels, especially concerning the adoption of artificial intelligence technologies. Tailored strategies are essential to align technological integration with institutional goals.